2013
DOI: 10.1016/j.cmet.2013.03.017
|View full text |Cite
|
Sign up to set email alerts
|

WNT-LRP5 Signaling Induces Warburg Effect through mTORC2 Activation during Osteoblast Differentiation

Abstract: Summary WNT signaling controls many biological processes including cell differentiation in metazoans. However, how WNT reprograms cell identity is not well understood. We have investigated the potential role of cellular metabolism in WNT-induced osteoblast differentiation. WNT3A induces aerobic glycolysis known as Warburg effect by increasing the level of key glycolytic enzymes. The metabolic regulation requires LRP5 but not β-catenin, and is mediated by mTORC2-AKT signaling downstream of RAC1. Suppressing WNT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
306
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 306 publications
(327 citation statements)
references
References 60 publications
20
306
1
Order By: Relevance
“…Future studies are warranted to explore these potential mechanisms. Finally, in addition to hypoxia and HIFα stabilization, WNT signaling, a well-known mechanism for stimulating bone anabolism, also induces aerobic glycolysis during osteoblast differentiation (33). Thus, increased glycolysis may represent a general mechanism for osteoblast differentiation in response to various physiologic stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies are warranted to explore these potential mechanisms. Finally, in addition to hypoxia and HIFα stabilization, WNT signaling, a well-known mechanism for stimulating bone anabolism, also induces aerobic glycolysis during osteoblast differentiation (33). Thus, increased glycolysis may represent a general mechanism for osteoblast differentiation in response to various physiologic stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study (53) reported that Wnt-Lrp5 signaling also regulates glucose metabolism in osteoblasts. In this context, Wnt3a signaling through Lrp5 in cell lines characteristic of osteoprogenitors activated mTORC2-Akt signaling to increase the conversion of glucose to lactate via the Warburg effect.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanism might not be through archetypal gene expression changes of a narrow set of target genes. Rather, Wnt signaling roles might promote, for example, a cellular metabolic state (Esen et al, 2013), or asymmetric cell divisions (Habib et al, 2013) that generally curtail differentiation. Regardless, the consequences of canonical Wnt inhibition on valve development highlight how both increased and decreased Wnt activity could cause various manifestations of congenital valve disease.…”
Section: Wnt Signaling and Developmental Transitions During Valvulogementioning
confidence: 99%